Hommage national à Ernest Solvay : inauguration du monument 16 octobre 1932 - Hymans, Paul; Mac, Adolphe; Langevin, Paul (Bruxelles : J.-E. Goossens, 1933)
Bibliotheek E. Anseele
Frans
Monografie
Keywords: Solvay, Ernest